From Environmental Destruction To Sustainability: A Systematic Review Of Green Human Resource Development In Manufacturing Companies - Hafidz, Sholeh; Makarim, Muhammad Harfiansyah (JURNAL ILMU MANAJEMEN, 2025)
Environmental degradation caused by manufacturing activities has become a major global concern, driving the need for sustainable transformation within the industrial sector. This study aims to systematically review the role of Green Human Resource Development (GHRD) in facilitating the transition from environmental destruction to sustainability in manufacturing companies. Using the Systematic Literature Review (SLR) method guided by the PRISMA framework, this research analyzed 1,670 Scopus-indexed articles published between 2020 and 2025, of which 15 met the inclusion criteria. The findings reveal that GHRD acts as a strategic mechanism that connects environmental management policies with employee behavior and organizational performance. Through green recruitment, training, and performance appraisal, GHRD develops employees’ environmental competencies, strengthens green leadership, and fosters sustainability-oriented organizational cultures. The synthesis of previous studies demonstrates that GHRD enhances sustainable performance by promoting innovation, energy efficiency, waste reduction, and green technological adoption. Furthermore, the transformation from environmental degradation to sustainability is primarily driven by human capacity building and eco-conscious organizational culture rather than by technology alone. This review concludes that integrating GHRD into manufacturing management systems is essential to achieving a balanced alignment between economic growth, social responsibility, and environmental preservation, positioning human resources as the key catalyst for sustainable industrial transformation.